Transatlantic burden sharing: suggesting a new research agenda. Issue 4 (2nd October 2018) - Zyla, Benjamin
ABSTRACT: Current studies on NATO burden sharing are only able to show some weak statistical trends between selective variables; they are unable to explain and show why this trend exists and why it occurred at particular times (or not). This is due to the dominant deductive and hypothesis testing research designs that prevent researchers to produce richer causal explanations or intersubjective understandings of how states, for example, construct and assign meaning to burdens or what forms of social representation, values, norms and ideals influence the making of (national) burden sharing decisions. Thus, we charge, the literature needs to adopt an eclecticist approach to studying NATO burden sharing – that is to combine rationalist with sociological approaches and methodologies highlighting the importance of intersubjective meanings and the role of social forces, norms, beliefs, and values. The article lays out what such a research programme might look like and how one could operationalise it.